2014
DOI: 10.1007/s00038-014-0636-9
|View full text |Cite
|
Sign up to set email alerts
|

Supportive communication with parents moderates the negative effects of electronic media use on life satisfaction during adolescence

Abstract: Communication with parents seems to buffer the negative effects of EM use on LS during adolescence. Higher computer use was related to lower LS, but "optimal" frequency of EM communication with friends was country specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 38 publications
2
37
0
2
Order By: Relevance
“…HBSC has been conducted at four-year intervals since 1983/1984 in a growing number of countries. Its methodology is based on the WHO recommendations and all countries follow the same research protocol in terms of sampling, questionnaire items and survey administration (7,8,11,30). The Czech Republic has been participating since 1994.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HBSC has been conducted at four-year intervals since 1983/1984 in a growing number of countries. Its methodology is based on the WHO recommendations and all countries follow the same research protocol in terms of sampling, questionnaire items and survey administration (7,8,11,30). The Czech Republic has been participating since 1994.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also demonstrated that LS is related to age, gender, material and housing circumstances, family and school environment, and socioeconomic status (6)(7)(8)(9)(10)(11)(12)(13). Furthermore, LS in adolescents is strongly influenced by life experiences, social relationships, stress and anxiety, social competence and good coping skills, self-esteem, self-acceptance, the ability to love oneself, optimism, and individual spirituality (7,8,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Supportive communication between parents and early adolescents has been shown to offset the negative effects (e.g., reduced life satisfaction) of using electronic media (Boniel-Nissim et al, 2015). Moreover, van den Eijnden et al (2010) report that “qualitatively good communication” (p. 77) about internet use on the part of parents decreased the likelihood of their adolescent children developing compulsive internet-related behaviors.…”
Section: The Home: a Significant Context Of Developmentmentioning
confidence: 99%
“…34 In some samples, communication with existing friends via electronic devices has been associated with positive outcomes. 34,35 Research has shown that many connections with nonfriends or with those with whom youth have weak friendship ties may be related to more cyberbullying and cybervictimization. 19 Although the level and type of involvement online and in social networking contexts varies, engagement with each other in online contexts is the norm among youth, and it is important for them to be savvy not about how to cyberbully but how to avoid it.…”
Section: Discussionmentioning
confidence: 98%